2020
DOI: 10.1111/raq.12484
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of marine mussels Mytilus edulis and M. galloprovincialis: systematic literature review of risk factors and recommendations for future research

Abstract: The aim of this study was to summarise the literature reporting the risk factors for mortality in the mussel species Mytilus edulis and Mytilus galloprovincialis in order to identify potential science-based solutions to prevent or mitigate mussel mortality outbreaks. We followed the PRISMA methodology: Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The studied corpus of 91 publications (114 studies) was highly heterogeneous with respect to the methodological approaches used to define or es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 119 publications
2
11
0
Order By: Relevance
“…Therefore, temperatures in our study are within the ecological relevant and even optimal range for this species. Recent meta-analysis also indicates that temperature threshold for long-term survival of M. edulis is ~20 °C (Lupo et al, 2020). Therefore, 20 °C appears to be close to the metabolic optimum of M. edulis, so rate-enhancing effects of temperature dominate over the potentially negative impacts on metabolism as long as warming occurs below the 20 °C threshold, as in our study.…”
Section: Effect Of Warming and Oa On Bioenergeticssupporting
confidence: 79%
“…Therefore, temperatures in our study are within the ecological relevant and even optimal range for this species. Recent meta-analysis also indicates that temperature threshold for long-term survival of M. edulis is ~20 °C (Lupo et al, 2020). Therefore, 20 °C appears to be close to the metabolic optimum of M. edulis, so rate-enhancing effects of temperature dominate over the potentially negative impacts on metabolism as long as warming occurs below the 20 °C threshold, as in our study.…”
Section: Effect Of Warming and Oa On Bioenergeticssupporting
confidence: 79%
“…The elevated SMR at 15°C seen in the present study, therefore, reflects the rate-enhancing effects of temperature on physiological and biochemical reactions such as activities of metabolic enzymes, ion channels, mitochondria, and other important bioenergetic processes (Hochachka, 1973). Recent meta-analysis also indicates that temperature threshold for long-term survival of M. edulis is ~20°C (Lupo et al, 2021).…”
Section: Effect Of Warming and Oa On Bioenergeticssupporting
confidence: 56%
“…The elevated SMR at 15°C seen in the present study, therefore, reflects the rate‐enhancing effects of temperature on physiological and biochemical reactions such as activities of metabolic enzymes, ion channels, mitochondria, and other important bioenergetic processes (Hochachka, 1973). Recent meta‐analysis also indicates that temperature threshold for long‐term survival of M. edulis is ~20°C (Lupo et al., 2021). Therefore, 20°C appears to be close to the metabolic optimum of M. edulis , so rate‐enhancing effects of temperature dominate over the potentially negative impacts on metabolism as long as warming occurs below the 20°C threshold, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In France, however, recurrent mass mortalities of mixtures of Mytilus edulis and Mytilus galloprovincialis have occurred the last decade. The reasons are still unclear, but Benabdelmouna and Ledu (2016) suggested genetic abnormalities due to hybridization whereas Lupo et al (2021) in their review suggested elevated SST (despite the higher temperature tolerance for M. galloprovincialis), predation, and pathogens. On the French coast around Boulogne-sur-Mer, a series of 4-5 heat waves caused a mass mortality of intertidal M. edulis in August 2018 when 50%-60% of the annual commercial value was lost (Seuront et al 2019).…”
Section: Northeast Atlantic Coastmentioning
confidence: 99%